Gold-nanoparticle-decorated glass microspheres - Gadomska, Katarzyna Maria; Lechner, Sebastian James; Spatz, Joachim P. (Particle & particle systems characterization, 2013)
Patterning of microspheres with well-dispersed metallic nanoparticles (NPs) is a challenging task owing to NPs' high agglomeration potential. Here, a simple, three-step method is presented to decorate glass beads with gold nanoparticles arranged in a quasi-hexagonal manner. Such nano-modified particulate materials can later on serve as catalysts or precursors, i.e., carriers of gold nanoparticles for fabrication of complex polymer composites.
Gesehen am 26.01.2021